Parents' Experiences and Perceptions of Healthcare Transition in Adolescents with Asthma: A Qualitative Study - Hyekyun Rhee; Lindsay Batek; Lynn Rew; Laurene Tumiel-Berhalter (MDPI AG, 2023)
Adolescence marks a significant transition from pediatric to adult healthcare, and parents play critical roles in supporting their adolescents with chronic conditions through this process. However, little is known about parents' experiences, perceptions, and needs during this healthcare transition. This qualitative study explores the experiences and perceptions of parents regarding the care transition of their 16-17-year-old adolescents with asthma. Nineteen mothers participated in either a focus group or individual interviews, and a content analysis was conducted on the data. Parents expressed negative emotions and various concerns about their teens' transition readiness and asthma management. A need for early transition training for both adolescents and parents was discussed. Overall, the complexity and challenges associated with the healthcare transition of adolescents with asthma take a toll on parents, particularly when their teens are not adequately prepared to manage asthma independently. Parents need appropriate anticipatory guidance regarding the transition and skills to navigate changing roles and negotiate asthma care responsibilities with their teens. Timely interventions and support strategies for both adolescents and parents are needed to ensure the successful healthcare transition of adolescents with asthma.